2D simulation of temperature distribution within large-scale PEM electrolysis stack based on thermal conductivity measurements - Eichner, Benedikt J.; Amiri, Mahshid N.; Burheim, Odne S.; Lamb, Jacob J. (Frontiers in Chemical Engineering, 2024)
Polymer electrolyte membrane electrolyser cells (PEMEC) are recognized as highly suitable for large-scale green hydrogen production from variable renewable sources. To enhance production rates in PEMECs, current densities have gradually increased, resulting in elevated heat generation within the electrolysis cells. Consequently, the consideration of thermal gradients within individual cells within the stacks becomes increasingly crucial. This study presents a 2D thermal numerical steadystate model of an industrial-sized PEMEC stack, predicting thermal gradients within the cells in both stacking direction and along the channels of the flow fields. Through-plane thermal conductivities were measured ex-situ for the titanium felt porous transport layer (PTL), Tion5-W PFSA membrane, and PEMEC catalyst layers (CLs). At a compaction pressure of 16 bar, the wet PTL exhibited a thermal conductivity of 2.7 ± 0.2 W m -1 K -1 , the wet membrane of 0.31 ± 0.01 W m -1 K -1 , and the wet CLs of 0.19 ± 0.03 W m -1 K -1 . When modelled, thermal gradients of 16.5 ± 0.6 K in parallel flow and 17.6 ± 0.5 K in counter-flow were predicted within cells with a 1 m² cell area, operating at 2 A cm -2 . The counter-flow arrangement demonstrated a 0.2% advantage in voltage efficiency. An increase in current density to 3 A cm -2 resulted in a 10 K rise in thermal differences in both parallel and counter-flow conditions. However, the use of a sintered PTL reduced thermal gradients by approximately 3.7 K at 2 A cm -2 . The simulation indicated a 20 to 40% increase in maximal thermal gradients within the stack compared to models using lumped properties within the cells, emphasizing the significance of considering in-cell thermal gradients at the stack level.